Migrants and Refugees in Europe Work Integration in Comparative Perspective - Baglioni, Simone; Calò, Francesca (Policy Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This book explores the labour market integration of migrants, refugees and asylum seekers across seven European countries: the Czech Republic, Denmark, Finland, Greece, Italy, Switzerland and the UK. Using empirical data from the Horizon2020 SIRIUS Project, it investigates how legal, political, social and personal circumstances combine to determine the work trajectory for migrants who choose Europe as their home.